Pilot investigation: randomized-controlled analog trial for alcohol and tobacco smoking co-addiction using contingency management. Issue 5 (August 2018) - Orr, Michael F.; Lederhos Smith, Crystal; Finlay, Myles; Martin, Samantha C.; Brooks, Olivia; Oluwoye, Oladunni A.; Leickly, Emily; McDonell, Michael; Burduli, Ekaterina; Barbosa-Leiker, Celestina; Layton, Matt; Roll, John M.; et al.
Abstract : Contingency management (CM) is associated with decreases in off-target drug and alcohol use during primary target treatment. The primary hypothesis for this trial was that targeting alcohol use or tobacco smoking would yield increased abstinence in the opposite, nontargeted drug. We used a 2 [CM vs. noncontingent control (NC) for alcohol]×2 (CM vs. NC for smoking tobacco) factorial design, with alcohol intake (through urinary ethyl glucuronide) and tobacco smoking (through urinary cotinine) as the primary outcomes. Thirty-four heavy-drinking smokers were randomized into one of four groups, wherein they received CM, or equivalent NC reinforcement, for alcohol abstinence, smoking abstinence, both drugs, or neither drug. The CM for alcohol and tobacco group had only two participants and therefore was not included in analysis. Compared with the NC for alcohol and tobacco smoking group, both the CM for the tobacco smoking group [odds ratio (OR)=12.03; 95% confidence interval (CI): 1.50–96.31] and the CM for the alcohol group (OR=37.55; 95% CI: 4.86–290.17) submitted significantly more tobacco-abstinent urinalyses. Similarly, compared with the NC for the alcohol and tobacco group, both the CM for smoking (OR=2.57; 95% CI: 1.00–6.60) and the CM for alcohol groups (OR=3.96; 95% CI: 1.47–10.62) submitted significantly more alcohol-abstinent urinalyses. These data indicate cross-over effects of CM on indirect treatment targets. Although this is a pilot investigation, it could help to inform the design of novel treatments for alcohol and tobacco co-addiction. Abstract : Supplemental Digital Content is available in the text.